INSURANCE COMPANIES AS PRODUCERS OF INVESTMENT FINANCIAL SERVICES - TKACHENKO, Nataliia; KYRYLENKO, Serhiy (Scientific journal «World of Finance», 2023)
Introduction. Insurance companies are among the largest investors in countries with developed insurance markets. At the same time, it is legitimate to consider them as institutional investors. In today’s conditions, foreign insurance companies demonstrate the intensification of life insurance, which, in turn, determines the need to improve existing insurance products and/or introduce non-traditional products, which include investment life insurance. The latter are a popular instrument in the market of insurance and investment services, primarily due to the combination of such features as insurance protection and profitability. The successful operation of life-insurers in a constantly dynamic and competitive environment is associated with their ability to quickly respond to the challenges of the external and internal environments, and not only to adapt to them, but also to use new circumstances for increasing the competitiveness and capitalization of the company, as well as preserving and expansion of own client base. The purpose of the article is to study the specifics of the activity of insurers as institutional investors, on the one hand, and their ability to produce investment financial services, in particular investment life-insurance services, to identify the attributes of the latter, differences from classical life insurance and outline the prospects for the development of investment-oriented life insurance on the domestic insurance market. Results. It is identified the features of the functioning of insurance companies as institutional investors. The definition of “investment potential of an insurance company” was defined and deepened. The specifics of investing insurance reserve funds and investment opportunities for non-life and life insurers are argued. Modern trends in the development of the life insurance market and, accordingly, the latest formats in the management of assets of life insurers have been revealed. The specifics of investment life insurance are clarified and its attributes are formulated. The differences between classic mixed life insurance and investment life insurance are systematized according to the following criteria: motivation for concluding the contract; placement of insurance premium; the principle of calculating insurance premiums; obligations of the insurer; the amount of the redemption amount; the possibility of receiving additional payments; the dynamics of increasing the premium reserve. Trends in the development of investment life insurance in Europe and on the Polish insurance market have been analyzed. Conclusions. Modernity requires the implementation of the latest approaches to the activities of insurance companies, in particular in the area of production of investment financial services, namely investment life insurance. Classical standards in life insurance are gradually being abandoned, which contributes to the dynamic development of insurance worldwide, which provides for the payment of insurance coverage depending on the dynamics of stock values. The need to develop investment life insurance on the domestic insurance market – a financial instrument that embodies both insurance protection and an accumulation opportunity with the help of investments – has been proven.